Implementasi Manajemen Sarana dan Prasarana Dalam Meningkatkan Mutu Pendidikan di MTs Negeri 1 Lebak - Torismayanti Torismayanti; Anis Zohriah; Abdul Muin (Journal on Education, 2023)
This study aims to: Describe, constraints, and solutions from the Implementation of Facilities and Infrastructure Management in Improving the Quality of Education at MTs Negeri 1 Lebak. This research was conducted using a qualitative approach. Data collection techniques in this study used observation, interviews and documentation. The data obtained was then analyzed using qualitative data analysis consisting of: (a) data reduction, (b) data presentation, and (c) drawing conclusions. The research results show that: 1) Planning for facilities and infrastructure at MTs Negeri 1 Lebak, namely coordination meetings, determining the madrasah program, and determining needs. 2) Procurement of facilities and infrastructure at MTs Negeri 1 Lebak, namely carried out by the facilities and infrastructure, then proceed to the Head of TU and known by the Head of Madrasah to submit a proposal to the government 3) Arrangement of facilities and infrastructure at MTs Negeri 1 Lebak, namely proper maintenance by all residents of the madrasa accompanied by a list of persons in charge. 4) The use of facilities and infrastructure at MTs Negeri 1 Lebak, namely scheduling, but the obstacle faced is that the madrasa has 2 separate buildings, making it difficult for the learning process 5) Removal of facilities and infrastructure at MTs Negeri 1 Lebak, which is carried out by means of auctions and grants